A Comparison of Pediatric vs. Adult Patients with the Ewing Sarcoma Family of Tumors - Verma, Vivek; Denniston, Kyle A.; Lin, Christopher J.; Lin, Chi (Frontiers in Oncology, 2017)
PURPOSE: This study sought to identify differences in clinical characteristics, outcomes, and treatments between adult and pediatric patients with Ewing sarcoma family of tumors (ESFT). METHODS: Using the Surveillance, Epidemiology, and End Results Database from 1983-2013, 1,870 patients were analyzed (n=976 pediatric, n=894 adult). Between the two groups, demographic, tumor, and treatment characteristics were collated and compared. The chi-squared test determined differences in proportions of the variables between groups. Survival analysis was done by the Kaplan-Meier method; distributions were compared using the log-rank test. Univariate and multivariate analyses were performed in order to examine variables correlating with overall survival (OS), the primary endpoint. RESULTS: Adult patients had a poorer prognosis and were more likely to present with PNET histology, along with distant metastasis and soft tissue primary site. In patients undergoing surgery, RT was not associated with higher OS in either children or adults. If no surgery was performed, receipt of RT was associated with higher OS in adults but not children. Adulthood negatively correlated with OS on multivariate analysis when adjusting for potential confounding factors. Other salient factors associated with OS were male gender, metastatic disease, non-extremity bone location, treatment era, and PNET histology. However, when examining the most recent subset (patients treated 2004-2013), RT was associated with improved OS in both pediatrics and adults, which was an independent predictor on multivariate analysis. CONCLUSIONS: Adult patients with ESFT have inferior survival as compared to pediatric patients, likely related to earlier clinical detection in the latter.